Veterinary differentiation: how veterinary education can adequately support the developing profession - Wendela Wapenaar (Universitat Politècnica de València, 2015)
We are in a pivotal point in time for the veterinary medical education. A decision to broaden the scope and potential of veterinary medical education is fundamental for the profession to navigate a transition into a sustainable future. Leadership, collaboration and a shared vision will determine the destiny of the profession. Knowledge expansion in the veterinary field is challenging the training of omnicompetent vets. Veterinary medical education can adequately support the developing profession by implementing a differentiation in their programmes to answer the demand of society in a sustainable way. By training vets to be more competent in either companion animal or food animal medicine one might positively influence the vets' confidence, which can help to improve their communication with clients and improve mental wellbeing. This article describes current challenges in the profession and the opportunities for differentiation in veterinary education to combat these challenges.